Baby boomers of color : implications for social work policy and practice - Delgado, Melvin (Columbia University Press, 2015)
Because researchers often treat baby boomers of color as belonging to one group, quality data on the individual status of specific racial populations is lacking, leading to insufficiently designed programs, policies, and services. The absence of data is a testament to the invisibility of baby boomers of color in society and deeply affects the practice of social work and other helping professions that require culturally sensitive approaches. Melvin Delgado rectifies this injustice by providing a comprehensive portrait of the status and unique assets of boomers of color.